Finite Element Crash Simulations and Impact-Induced Injuries - Jaroslav Mackerle (Shock and Vibration)
This bibliography lists references to papers, conference proceedings and theses/dissertations dealing with finite element simulations of crashes, impact-induced injuries and their protection that were published in 1980–1998. 390 citations are listed.